Perancangan Robot Manipulator Pindah Tanam pada Hidroponik dengan Metode Inverse Kinematics berbasis Arduino - Rifqi Alvaro; Hurriyatul Fitriyah; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Hydroponics is a method of planting by using minimum land that uses a substitute medium other than soil as the planting medium. The stages of planting in hydroponics have the same method as planting on lands such as the seedling and planting process. The process of planting uses rockwool and netpot containers as the media. In this research, the writer creates a design of a robot manipulator that is convenient for the transplanting process in hydroponics. The robot manipulator has 4 Degree of Freedom that can carry out the netpot removal process for lifting and moving the plants. The design of the device used in the system is a Dynamixel AX-12A servo. The printing system uses ABS material with the thickness of an arm is 3 mm and an end-effector is 2 mm. Diameter of the netpot is 5cm. The length of the first arm of the robot manipulator is 21 cm, the second arm is 21 cm and the end-effector is 12.5 cm with a total length of 54.5 cm. The torque measurement of the arm that is applied to the first servo arm when a sprout that has a 20-gram load is lifted, is 0.6174 N/m. Testing the accuracy of the system in the transplanting process was 97.5% successful in testing using sprout loads. The average computation time of the system for each coordinate is 42.1ms. The total computation time required by the system in moving 4 objects along with the delay is 97640ms.